A Coordinated Dispatch Method for Receiving-end Grid Considering HVDC Power Characteristics. Issue 1 (February 2021) - Jiao, Shumei; Chen, Yuanyang; Cao, Yijia; Liao, Changfeng; Tan, Yi; Li, Yong; Zeng, Zilong; Guo, Siyuan
Abstract: The power injection from the high-voltage direct current (HVDC) transmission system has a significant impact on the operation and scheduling of the receiving-end power system. In this paper, considering the unipolar blocking faults and the power characteristics of the traditional HVDC system (i.e., LCC-HVDC), a multi-period dispatch model is proposed for the receiving-end power system to achieve the coordinated optimization of various dispatchable resources such as the power injection of LCC-HVDC and the local generation. In the proposed model, the constraints such as those related to the number of LCC-HVDC power adjustments, branch power flow, bus voltage and the output of local generators are taken into account, and its objective is to minimize the total power purchase cost of the receiving-end power system. To solve the proposed model efficiently, the method for determining the time of changing LCC-HVDC power injection is first proposed, and then its results are used to further solve the proposed multi-period dispatch model of the receiving-end power system. The simulation results show that the dispatch method proposed in this paper can effectively deal with LCC-HVDC unipolar blocking faults, and reasonably optimize the power purchase cost of the receiving-end power system.